PENGARUH KUALITAS PELAYANAN DIVISI SALES TERHADAP KEPUASAN PELANGGAN DI PT NIPRESS, Tbk - ., Muhlis; Mediterania, Siska (Economicus, 2020)
This study aims to determine the quality of service sales division of customer satisfaction at PT. Nipress, Tbk. This study uses a questionnaire as an instrument to take a sample of 77 respondents, who are customers at PT. Nipess, Tbk. Data analysis uses multiple linear regression. The results of data analysis using multiple linear regression showed that the reliability variable partially had a significant effect on customer satisfaction at PT. Nipress, Tbk. Simultaneously tangibles,, reliability, responsiveness, assurance and empathy have a significant effect on customer satisfaction. The magnitude of the influence of tangibles, reliability, responsiveness, assurance and empathy variables is 47.3% while the rest is influenced by other variables not discussed in this study.